2018
DOI: 10.1063/1.5039458
|View full text |Cite
|
Sign up to set email alerts
|

CHD3 dissociation on Pt(111): A comparison of the reaction dynamics based on the PBE functional and on a specific reaction parameter functional

Abstract: We present a comparison of ab initio molecular dynamics calculations for CHD dissociation on Pt(111) using the Perdew, Burke and Ernzerhof (PBE) functional and a specific reaction parameter (SRP) functional. Despite the two functionals predicting approximately the same activation barrier for the reaction, the calculations using the PBE functional consistently overestimate the experimentally determined dissociation probability, whereas the SRP functional reproduces the experimental values within a chemical accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…Another important dynamical aspect of the reaction of methane is the energy transfer from the molecule to the surface. 54 Figure 6 compares for scattered trajectories this energy transfer from CHD 3 to Cu(111), 54 Pt(111), 65 Ni(111), 12 and Pd(111), where the energy transfer E T is defined aswhere V and K are the potential free and kinetic energy of methane at the initial (i) and final (f) steps of the scattered trajectories, respectively. In general, it is observed that the lower the surface atom mass is, the higher the energy transfer is from methane to the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Another important dynamical aspect of the reaction of methane is the energy transfer from the molecule to the surface. 54 Figure 6 compares for scattered trajectories this energy transfer from CHD 3 to Cu(111), 54 Pt(111), 65 Ni(111), 12 and Pd(111), where the energy transfer E T is defined aswhere V and K are the potential free and kinetic energy of methane at the initial (i) and final (f) steps of the scattered trajectories, respectively. In general, it is observed that the lower the surface atom mass is, the higher the energy transfer is from methane to the surface.…”
Section: Resultsmentioning
confidence: 99%
“…As in a previous study on CHD 3 dissociation on platinum surfaces, 14,23,29,52 we make use of the SRP32-vdW exchange correlation functional, defined as 21…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…26 It was suggested that this was due to the functional not including van der Waals correlation, which has been shown to be necessary previously for giving accurate descriptions of dissociation dynamics. 14,27 The transferability of an SRP functional amongst different metals of the same group (group 10) of the periodic table has been demonstrated for methane dissociation, where the same SRP functional gives a chemically accurate description for the reaction of methane on Ni(111), 21,23,28 Pt(111), 23 and Pt(211). 23,29,30 This same SRP functional has recently been used to predict the reactivity of CHD 3 on Cu(111) and Cu(211), 31 and when experimental data become available, this will confirm whether the SRP functional is also transferable to methane dissociation on transition metals in other specific groups of the periodic table.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the topology of the potential might be very different, possibly resulting in a different dynamics, similarly to what was observed for CHD 3 on Pt(111). 66 Four angles have been used to characterize the molecular geometry: θ d , θ s , φ, and γ (sketched in Fig. 2).…”
Section: Resultsmentioning
confidence: 99%